GAMBARAN KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN DI RUANG RAWAT JALAN RSUD MEURAXA KOTA BANDA ACEH - Permatasari, Fani; Jannah, Noraliyatun; Mayasari, Putri (Jurnal Ilmiah Mahasiswa Fakultas Keperawatan, 2024)
Patient satisfaction is a very important indicator of all aspects, in providing care or nursing care we need to pay attention to patient satisfaction, if the patient is dissatisfied with the health services received it will be able to hinder the patients recovery. The purpose of this study was to find out patient satisfaction with health services in the outpatient ward of Meuraxa Hospital, Banda Aceh Municipality. In this research, a descriptive exploratory design with a cross sectional study approach was used. The population in this study were all outpatients at Meuraxa Hospital in Banda Aceh Municipality who were enthusiastic to be respondents during the predetermined study period and the sample in this study was 152 people. Data collection was carried out using a questionnaire developed from the theoretical concepts put forward by WHO (World Health Organization) regarding the quality of health services which emphasized the dimensions of effectiveness, efficiency, timeliness and integration. Univariate analysis data, with the results showing that patient satisfaction with health services in the outpatient room of the Meuraxa Hospital in Banda Aceh Municipality was almost entirely for the safe dimension, namely 151 patients (99.3%), followed by an effective dimension of 149 patients (98.0), the fair and integrated dimensions were 148 patients (97.4), the efficient dimensions were 147 patients (96.7), and finally the timely dimension was 144 patients (94.7). Health workers can pay attention to service times and arrival hours to the hospital so that patients are not bored waiting and dissatisfied with the services received.